logo

Recursive Relations of Legendre Polynomials 📂Functions

Recursive Relations of Legendre Polynomials

Theorem

Pl(x)=12ll!dldxl(x21)l(1) P_{l}(x)=\dfrac{1}{2^l l!} \dfrac{d^l}{dx^l}(x^2-1)^l \tag{1}

Such a Legendre Polynomial PlP_{l} satisfies the following recursive relation:

Pl+1(x)Pl1(x)=(2l+1)Pl(x)(a) P^{\prime}_{l+1}(x)-P^{\prime}_{l-1}(x)=(2l+1)P_{l}(x) \tag{a}

lPl(x)=(2l1)xPl1(x)(l1)Pl2(x)(b) lP_{l}(x)=(2l-1)xP_{l-1}(x)-(l-1)P_{l-2}(x) \tag{b}

xPl(x)Pl1(x)=lPl(x)(c) xP^{\prime}_{l}(x)-P^{\prime}_{l-1}(x)=lP_{l}(x)\tag{c}

Proof

(a)(a)

First, if we calculate the derivative of Pl(x)P_{l}(x),

ddxPl(x)=12ll!ddxdldxl(x21)l=12ll!dldxlddx(x21)l=2l2ll!dldxl[x(x21)l1]=12l1(l1)!dl1dxl1[(x21)l1+2(l1)x2(x21)l2]=12l1(l1)!dl1dxl1[(x21)+2lx22x2](x21)l2=12l1(l1)!dl1dxl1[(2l1)x21](x21)l2 \begin{align*} \frac{d}{dx}P_{l}(x) &= \frac{1}{2^l l!}\frac{d}{dx} \dfrac{d^l}{dx^l}(x^2-1)^l \\ &= \frac{1}{ 2^{l}l! }\frac{ d ^{l} }{ dx^{l} }\frac{d}{dx}(x^{2}-1)^{l} \\ &= \frac{2l}{ 2^{l}l! }\frac{ d ^{l} }{ dx^{l} }\left[ x(x^{2}-1)^{l-1} \right] \\ &= \frac{1}{ 2^{l-1}(l-1)! }\frac{ d ^{l-1} }{ dx^{l-1} }\left[ (x^{2}-1)^{l-1}+2(l-1)x^{2}(x^{2}-1)^{l-2} \right] \\ &= \frac{1}{ 2^{l-1}(l-1)! }\frac{ d ^{l-1} }{ dx^{l-1} }[(x^{2}-1)+2lx^{2}-2x^{2}] (x^{2}-1)^{l-2} \\ &= \frac{1}{ 2^{l-1}(l-1)! }\frac{ d ^{l-1} }{ dx^{l-1} }[(2l-1)x^{2}-1] (x^{2}-1)^{l-2} \end{align*}

and substitute l+1l+1 for ll,

Pl+1(x)=12l!dldxl[(2l+1)x21](x21)l1(2) P^{\prime}_{l+1}(x)=\frac{1}{2l!}\frac{ d ^{l} }{ dx^{l} }[(2l+1)x^{2}-1] (x^{2} -1 )^{l-1} \tag{2}

Then, substitute ll with l1l-1 into (1)(1) and differentiate,

Pl1(x)=12l1(l1)!ddxdl1dxl1(x21)l1=2l2ll!dldxl(x21)l1 \begin{align*} P^{\prime}_{l-1}(x) &= \frac{1}{2^{l-1}(l-1)!}\frac{d}{dx} \frac{ d^{l-1} }{ d x^{l-1} }(x^{2}-1)^{l-1} \\ &= \frac{2l}{2^{l}l!}\frac{ d^{l} }{ dx^{l} }(x^{2}-1)^{l-1} \tag{3} \end{align*}

Now, calculating (2)(3)(2)-(3),

Pl+1(x)Pl1(x)=12l!dldxl[(2l+1)x21](x21)l12l2ll!dldxl(x21)l1=12ll!dldxl[(2l+1)x2(2l+1)](x21)l1=12ll!dldxl(2l+1)(x21)l=2l+12ll!dldxl(x21)l \begin{align*} P^{\prime}_{l+1}(x)-P^{\prime}_{l-1}(x) &= \frac{1}{2l!}\frac{ d ^{l} }{ dx^{l} }[(2l+1)x^{2}-1] (x^{2}-1)^{l-1} -\frac{2l}{2^{l}l!}\frac{ d^{l} }{ dx^{l} }(x^{2}-1)^{l-1} \\ &= \frac{1}{2^{l}l!}\frac{ d ^{l} }{ d x^{l} }[(2l+1)x^{2}-(2l+1)] (x^{2}-1)^{l-1} \\ &= \frac{1}{2^{l}l!}\frac{ d ^{l} }{ d x^{l} }(2l+1)(x^{2}-1)^{l} \\ &= \frac{2l+1}{2^{l}l!}\frac{ d ^{l} }{ d x^{l} }(x^{2}-1)^{l} \end{align*}

Due to (1)(1), the right side is the same as (2l+1)Pl(x)(2l+1)P_{l}(x), hence

Pl+1(x)Pl1(x)=(2l+1)Pl(x) P^{\prime}_{l+1}(x)-P^{\prime}_{l-1}(x)=(2l+1)P_{l}(x)

(b)(b)

Generating Function of Legendre Polynomials

The function Φ(x,h)\Phi (x,h) below is called the generating function of Legendre Polynomials.

Φ(x,h)=112xh+h2,h<1 \Phi (x,h)=\frac{1}{\sqrt{1-2xh+h^{2}}},\quad |h|<1

The generating function satisfies the following equation:

Φ(x,h)=P0(x)+hP1(x)+h2P2(x)+=l=0hlPl(x) \Phi (x,h)=P_{0}(x)+hP_{1}(x)+h^{2}P_{2}(x)+\cdots =\sum \limits_{l=0}^{\infty}h^{l}P_{l}(x)

Part 2. Proof of Recursive Relation

First, differentiate Φ(x,t)\Phi (x,t) with respect to tt, Φt=12(2x+2t)(12xt+t2)32    (12xt+t2)Φt=(xt)Φ \begin{align*} && \frac{ \partial \Phi}{ \partial t } &= -\frac{1}{2}(-2x+2t)(1-2xt+t^{2})^{-\frac{3}{2}} \\ \implies && (1-2xt+t^{2})\frac{ \partial \Phi}{ \partial t} &= (x-t)\Phi \end{align*}

Then, substitute Φ(x,t)=l=0tlPl(x)\Phi (x,t)=\sum \limits_{l=0}^{\infty}t^{l}P_{l}(x) into the above equation,

(12xt+t2)l=1ltl1Pl(x)=(xt)l=0tlPl(x) (1-2xt+t^{2})\sum \limits _{l=1}^{\infty}lt^{l-1}P_{l}(x)=(x-t)\sum\limits_{l=0}^{\infty}t^{l}P_{l}(x)

Aligning the indices,

(12xt+t2)l=0(l+1)tlPl+1(x)=(xt)l=0tlPl(x) (1-2xt+t^{2})\sum \limits _{l=0}^{\infty}(l+1)t^{l}P_{l+1}(x)=(x-t)\sum\limits_{l=0}^{\infty}t^{l}P_{l}(x)

This equation is an identity with respect to tt, so the coefficients of tlt^{l} on both sides must be the same. Comparing the coefficients of tlt^{l},

1[(l+1)tlPl+1(x)]2xt[(l)tl1Pl(x)]+t2[(l1)tl2Pl1(x)]=x[tlPl(x)]t[tl1Pl1(x)] 1 [(l+1)t^{l}P_{l+1}(x)] -2xt[(l)t^{l-1}P_{l}(x)]+t^{2}[(l-1)t^{l-2}P_{l-1}(x)]=x [t^{l}P_{l}(x)]-t[t^{l-1}P_{l-1}(x)]

    (l+1)tlPl+1(x)2xltlPl(x)+(l1)tlPl1(x)=xtlPl(x)tlPl1(x) \implies (l+1)t^{l}P_{l+1}(x) -2xlt^{l}P_{l}(x)+(l-1)t^{l}P_{l-1}(x)=x t^{l}P_{l}(x)-t^{l}P_{l-1}(x)

    (l+1)Pl+1(x)2xlPl(x)+(l1)Pl1(x)=xPl(x)Pl1(x) \implies (l+1)P_{l+1}(x) -2xlP_{l}(x)+(l-1)P_{l-1}(x)=x P_{l}(x)-P_{l-1}(x)

Here, if we substitute l1l-1 for ll,

lPl(x)2x(l1)Pl1(x)+(l2)Pl2(x)=xPl1(x)Pl2(x) lP_{l}(x) -2x(l-1)P_{l-1}(x)+(l-2)P_{l-2}(x)=x P_{l-1}(x)-P_{l-2}(x)

And rearrange the left side with respect to Pl(x)P_{l}(x),

lPl(x)=(2l1)xPl1(x)(l1)Pl2(x) lP_{l}(x) =(2l-1)x P_{l-1}(x)-(l-1)P_{l-2}(x)

(c)(c)

It is easy to verify that the generating function satisfies the following:

(xh)Φx=hΦh (x-h)\frac{ \partial \Phi}{ \partial x }=h\frac{ \partial \Phi}{ \partial h }

Now, substituting the series form Φ(x,h)=l=0hlPl(x)\Phi (x,h)=\sum\limits_{l=0}^{\infty}h^{l}P_{l}(x) of the generating function,

(xh)l=0hlPl(x)=hl=1lhl1Pl(x) (x-h)\sum\limits_{l=0}^{\infty}h^{l}P^{\prime}_{l}(x)=h\sum\limits_{l=1}^{\infty}lh^{l-1}P_{l}(x)

The above equation is an identity with respect to hh, hence the coefficients of hlh^{l} on both sides must be the same. Comparing the hlh^{l} terms of both sides,

x[hlPl(x)]h[hl1Pl1(x)]=h[lhl1Pl(x)]    hl[xPl(x)Pl1(x)]=hllPl(x)    xPl(x)Pl1(x)=lPl(x) \begin{align*} && x[h^{l}P^{\prime}_{l}(x)]-h[h^{l-1}P^{\prime}_{l-1}(x)] = h[lh^{l-1}P_{l}(x)] \\ \implies && h^{l}[xP^{\prime}_{l}(x)-P^{\prime}_{l-1}(x)] = h^{l}lP_{l}(x) \\ \implies && xP^{\prime}_{l}(x)-P^{\prime}_{l-1}(x) = lP_{l}(x) \end{align*}